The 6-Month Antibody Durability of Heterologous Convidecia Plus CoronaVac and Homologous CoronaVac Immunizations in People Aged 18–59 Years and over 60 Years Based on Two Randomized Controlled Trials in China - Hudachuan Jiang; Pengfei Jin; Xiling Guo; Jiahong Zhu; Xue Wang; Peng Wan; Jingxuan Wan; Jingxian Liu; Jingxin Li; Fengcai Zhu (Vaccines, 2023)
Previous reports have shown that heterologous boosting with the AD5-vectored COVID-19 vaccine Convidecia based on a primary series of two doses of inactivated vaccine induces increasing immune responses. However, the immune persistence until 6 months after the heterologous prime-boost immunization was limited. Participants were from two single-center, randomized, controlled, observer-blinded trials, which involved individuals of 18–59 years of age and over 60 years of age. Eligible participants who previously primed with one dose or two doses of CoronaVac were stratified and randomly assigned to inoculate a booster dose of Convidecia or CoronaVac. Neutralizing antibodies against a live SARS-CoV-2 prototype virus and Delta and Omicron (B.1.1.529) variants, pseudovirus neutralizing antibodies against Omicron BA.4/5 variants, and anti-SARS-CoV-2 RBD antibodies at month 6 were detected, and the fold decreases and rate difference were calculated by comparing the levels of antibodies at month 6 with the peak levels at month 1. The neutralizing antibody titers against prototype SARS-CoV-2, RBD-specific IgG antibodies, and the Delta variant in the heterologous regimen of the CoronaVac plus Convidecia groups were significantly higher than those of the homologous prime-boost groups. In three-dose regimen groups, the geometric mean titers (GMTs) of neutralizing antibodies against prototype SARS-CoV-2 were 30.6 (95% CI: 25.1; 37.2) in the heterologous boosting group versus 6.9 (95% CI: 5.6; 8.6) in the homologous boosting group (p < 0.001) at month 6 in participants aged 18–59 years, and in the two-dose regimen, the neutralizing antibody GMTs were 8.5 (95% CI: 6.2; 11.7) and 2.7 (2.3 to 3.1) (heterologous regimen group versus CoronaVac regimen group, p < 0.001). Participants aged over 60 years had similar levels of neutralizing antibodies against the prototype, with GMTs of 49.1 (38.0 to 63.6) in the group receiving two doses of CoronaVac plus one dose of Convidecia versus 9.4 (7.7 to 11.4) in the group receiving three doses of CoronaVac (p < 0.001) and 11.6 (8.4 to 16.0) in the group receiving one dose of CoronaVac and one dose of Convidecia versus 3.3 (2.7 to 4.0) in the group receiving two doses of CoronaVac (p < 0.001). Compared with day 14, over sixfold decreases in neutralizing antibody GMTs were observed in the heterologous groups of the three- or two-dose regimen groups of younger and elderly participants, while in the homologous regimen groups, the GMTs of neutralizing antibodies decreased about fivefold in the two age groups. The heterologous prime-boost regimen with two doses of CoronaVac and one dose of Convidecia was persistently more immunogenic than the regimen of the homologous prime-boost with three doses of CoronaVac.